Greener from a Distance - Nfon, Charles (Book collections on Project MUSE., 2013)
Albert's life dream is to immigrate to the USA, to seek greener pastures. After several failed attempts, he finally gets a visa. Then he arrives the USA hoping for a bright and easy future. Before long he hears stories of desperation, struggles and a few successes. Desperation is portrayed by Mola aka Mboma who adopts a dead man's identity in order to stay in the USA and by Bruno who marries a US-born woman as his ticket to the USA, knowing fully well that she was leading a double life. Struggles are seen in Paul and Matt who have to work more than two times harder to barely survive in the USA. However, Samson, the surgeon is an example of a success story. Albert has to decide whether to stay in the USA, concoct a story for asylum and chase the dream that has proven elusive for many, or go back to his reality in Cameroon. Though the pasture may actually be greener on the other side for some, it takes a tremendous amount of work and dedication to keep it that way. Realising that the life in the Diaspora is not a bed of roses as portrayed by some Cameroonians, he decides to return to his modest job in Cameroon. Although this book could be considered a cautionary tale about immigration, it is also about the corruption that has overtaken Cameroon and its people.